2017
DOI: 10.5455/medarh.2017.71.110-114
|View full text |Cite
|
Sign up to set email alerts
|

Critical Carotid Artery Stenosis in Coronary and Non-Coronary Patients - Frequency of Risk Factors

Abstract: Introduction:Stroke is one of the largest socio medical problems of modern times. In addition to the third leading cause of death, it is the first cause of non-trauma disability. Numerous studies show a correlation of risk factors and arteriosclerotic lesions in the coronary arteries and carotid arteries.Patients and methods:Study was conducted at the Clinical Center University of Sarajevo, Clinic for Cardiology surgery, methodologically cross-sectional study and partly manipulative and clinical prevention stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
2
7
0
1
Order By: Relevance
“…In this context, a study was conducted by the American Heart Association, and it was reported that critical carotid artery stenosis is more often present in patients with coronary artery disease, while the association of risk factors has been demonstrated for diabetes, hypertension, and dyslipidemia. 26 While researching the risk factors for carotid artery stenosis, a study conducted by Evans 27 concluded that advanced age, tobacco smoking, hyperlipidemia, hypertension, diabetes, and physical inactivity are also factors contributing to the development of carotid stenosis, and women are relatively more at risk to develop carotid stenosis as compared to males. This patient was found to have a CCA stenosis of more than 90%, and therefore, the blood flow velocity was decreased beyond the stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a study was conducted by the American Heart Association, and it was reported that critical carotid artery stenosis is more often present in patients with coronary artery disease, while the association of risk factors has been demonstrated for diabetes, hypertension, and dyslipidemia. 26 While researching the risk factors for carotid artery stenosis, a study conducted by Evans 27 concluded that advanced age, tobacco smoking, hyperlipidemia, hypertension, diabetes, and physical inactivity are also factors contributing to the development of carotid stenosis, and women are relatively more at risk to develop carotid stenosis as compared to males. This patient was found to have a CCA stenosis of more than 90%, and therefore, the blood flow velocity was decreased beyond the stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that miR-483-5p is independently associated with new-onset diabetes mellitus and cardiovascular disease ( 17 ). Besides, it is well known that dyslipidemia is a risk factor for the development of CAS ( 38 ). The present study demonstrated that miR-483-5p expression levels were significantly associated with dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…According to Vranic (2017), the factors that play a major role in the pathogenesis and prediction of treatment for cardiovascular and cerebrovascular diseases are: hyperlipidemia, diabetes mellitus, hypertension, and smoking [12]. It has been reported that patients undergoing coronary bypass surgery usually have atherosclerosis in the carotid artery.…”
Section: Introductionmentioning
confidence: 99%